Sustainable Compact City as an Urban Sprawl Arrangement Concept in Penatih Dangin Puri, Denpasar - Ratmayanti, Putu Pradnya Lestari; Prajnawrdhi, Tri Anggraini; Trimarianto, Ciptadi (Journal of A Sustainable Global South, 2023)
The population growth in Denpasar City is happening very rapidly due to several factors and aspects of population. The growing number of people living in urban areas with aspects of life that take place continuously causes the city to no longer be able to accommodate all aspects of population activities. Therefore, there has been development in suburban areas such as Penatih Dangin Puri Village, which has become a location for filling space for an increasing population with various positive and negative impacts, one of which is the urban sprawl. To reduce the negative impact that occurs due to urban sprawl, the concept of sustainable compact city is the solution. The concept of Sustainable Compact City aims to reduce the use of conversion of agricultural land to non-agricultural land, reduce dependence on private transportation, empower public transportation, increase green open space, and make it easier for people to enjoy other public facilities. This concept is then expected to be able to produce the right strategy in accommodating all changes and indirectly control growth and be able to control the problems that arise due to the existence of this Urban Sprawl. Seeing these problems, the concept of Sustainable Compact City can be a concept for dealing with Urban Sprawl in the Penatih Dangin Puri village area, Denpasar City, which cannot be prevented from growing until now. Keywords: Urban Sprawl, Sustainable, Compact City, suburban area, structuring, land conversion.